2020
DOI: 10.1108/wwop-02-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trauma-focused cognitive behavior therapy on depression and the quality of life of the elderly in Indonesia

Abstract: Purpose This study aimed to analyze the effect of Trauma-Focused Cognitive Behavior Therapy (TF-CBT) on the depression level and quality of life of the elderly in an earthquake-affected district of North Lombok Regency, Indonesia. Design/methodology/approach A Randomized Controlled Trial (RCT) with a population of two elderly groups living in an earthquake-affected district was used in this study. The intervention comprised giving TF-CBT. There were three research instruments applied to determine the variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The interventions were predominantly delivered by health or social care professionals ( n = 11) [ 8 , 9 , 26 , 30 , 34 , 40 , 46 – 50 , 53 ], trained lay volunteers ( n = 5) [ 39 , 54 , 56 , 57 , 60 ] and research team members with a lack of qualification description [ 10 , 21 , 22 , 25 , 29 , 31 , 33 , 35 – 38 , 41 , 45 ]. In the Carandang et al [ 43 ] study, the intervention involved the older adults themselves participating in a volunteer activity (assist in behaviour change and engaging with community) whereas Borbon-Castro et al [ 42 ] involved Higher Education students in physical activity and sport discipline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interventions were predominantly delivered by health or social care professionals ( n = 11) [ 8 , 9 , 26 , 30 , 34 , 40 , 46 – 50 , 53 ], trained lay volunteers ( n = 5) [ 39 , 54 , 56 , 57 , 60 ] and research team members with a lack of qualification description [ 10 , 21 , 22 , 25 , 29 , 31 , 33 , 35 – 38 , 41 , 45 ]. In the Carandang et al [ 43 ] study, the intervention involved the older adults themselves participating in a volunteer activity (assist in behaviour change and engaging with community) whereas Borbon-Castro et al [ 42 ] involved Higher Education students in physical activity and sport discipline.…”
Section: Resultsmentioning
confidence: 99%
“…One way of addressing this barrier can be by providing support outside of dedicated health services which is integrated into the local community and local contexts. There is a growing evidence base on such psychosocial, community-based interventions in various different countries, delivering support to older adults via established forms of intervention such as Cognitive Behavioural Therapy [ 7 , 8 ] or educational interventions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Negative consequences of PTSD among older people ranged from psychiatric disorders to cognitive and physical health problems 13 . Moreover, the authors found trauma-focused cognitive behavioral therapy (TF-CBT) is an effective intervention for the elderly to reduce depression and improve their quality of life 14 . Despite the availability of effective treatment, the provision of PTSD services for the elderly following post-disaster still requires policy support to ensure its sustainability and widespread implementation.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Moreover, the authors found trauma-focused cognitive behavioral therapy (TF-CBT) is an effective intervention for the elderly to reduce depression and improve their quality of life. 14 Despite the availability of effective treatment, the provision of PTSD services for the elderly following post-disaster still requires policy support to ensure its sustainability and widespread implementation. Furthermore, existing policy for responding to the psychological needs among PTSD of the elderly in post-disaster situations is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, physical activity is considered to have a positive effect on reducing anxiety, stress, and depression, maintaining mental health, and ensuring psychological vitality. Besides, it improves the quality of life (17,18).…”
Section: Introductionmentioning
confidence: 99%